2006
DOI: 10.1111/j.1600-6143.2005.01227.x
|View full text |Cite
|
Sign up to set email alerts
|

Costimulation and Autoimmune Diabetes in BB Rats

Abstract: Costimulatory signals regulate T-cell activation. To investigate the role of costimulation in autoimmunity and transplantation, we studied the BB rat model of type 1 diabetes. Diabetes-prone BB (BBDP) rats spontaneously develop disease when 55-120 days of age. We observed that two anti-CD28 monoclonal antibodies (mAb) with different functional activities completely prevented diabetes in BBDP rats. Anti-CD154 mAb delayed diabetes, whereas treatment with CTLA4-Ig or anti-CD80 mAb accelerated disease. Anti-CD86 o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
14
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 73 publications
(70 reference statements)
2
14
0
Order By: Relevance
“…In the present study, we tested a more powerful and less pleiotropic approach of boosting Treg compared with histone deacetylase inhibition-stimulation with the CD28SA. Similar to previous studies in healthy mice 13 and various disease models, [15][16][17][18][19] CD28SA substantially increased the number of Treg in the periphery as well as in the brain. CD28SA …”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…In the present study, we tested a more powerful and less pleiotropic approach of boosting Treg compared with histone deacetylase inhibition-stimulation with the CD28SA. Similar to previous studies in healthy mice 13 and various disease models, [15][16][17][18][19] CD28SA substantially increased the number of Treg in the periphery as well as in the brain. CD28SA …”
Section: Discussionsupporting
confidence: 87%
“…13,14 Application of CD28SA in vivo effectively expands and potently activates polyclonal Treg. 13 In a variety of disease models, CD28SA reduced autoimmune reactions, [15][16][17] graft rejection, 18 and inflammation.…”
mentioning
confidence: 99%
“…8 Recently, studies in rodent autoimmune disease models have shown efficacy of supCD28 MAb treatment in the prevention of experimental autoimmune neuritis and experimental autoimmune encephalomyelitis with marked reduction of infiltrating cells and interferon (IFN)-␥ production, 9 adjuvant arthritis with amelioration of Th1/Th2 cell balance and induction of high IL-10 expression in synovia, 10 and in the Type 1 diabetes BB rat model with an increase of CD4 ϩ CD25 ϩ T-cell frequency. 11 In this study we show that in vivo application of supCD28 MAb to Lewis rats causes preferential expansion of Foxp3-expressing Treg cells over conventional T cells, and maintains not only their phenotype but also their potent regulatory functions against T-cell proliferation in response to mitogens, antibodies and allostimulation in vitro. Furthermore, using a full MHC-mismatch rat heterotopic heart transplantation model, we found that supCD28 MAb preferentially expands naturally occurring Treg (nTreg) cells and recruits these nTreg cells to the grafts, resulting in significant prolongation of cardiac graft survival.…”
mentioning
confidence: 56%
“…It was shown that restoration of the defect in regulatory T-cell function in BBDP rats by adoptive transfer with functional regulatory T cells from autoimmune diabetes-resistant BB rats, prevents autoimmune diabetes development [16][17][18]. Moreover, also in vivo expansion of Tregs in BBDP rats by super-agonistic αCD28 antibodies completely prevented autoimmune diabetes development [22].…”
Section: Discussionmentioning
confidence: 99%